Property trap in the digital era - I. V. Anokhov (Russian Journal of Economics and Law, 2020)
Objective: to identify trends in the use of property by entrepreneurs after the introduction of A. Harberger’s system and the complete digitalization of property relations.Methods: the article uses the methodology of the theory of inventive problem solving, which is used to assess the consequences of digitalization of property relations and the introduction of A. Harberger’s system.Results: having analyzed A. Harberger’s system, the author states that it is applicable only for the digitalization of property relations, since it provides maximum transparency of property rights, income generated by it, and the qualitative features of this property. A. Harberger’s system encourages the continuous transfer of property from one person to another, which can lead to a “no-property” regime. As a result, the entrepreneur’s property and profit-making techniques become publicly available, which undermines the foundations of entrepreneurship in the digital economy. Entrepreneurs find themselves in a property trap.Scientific novelty: in accordance with the methodology of the theory of inventive problem solving, the article identifies property objects classified by their functions: “engine”, “working body”, “transmission”, “computer”, and “energy source”. It is stated that the trends of technological improvement and digitalization turn the “computer” into the dominant factor of production, around which all production processes are built. This will increase its complexity, as well as the cost of purchasing and maintaining it. The production versatility of the “computer” will bring to the fore entrepreneurs who reduce the cost of the “computer” by providing its capacity for rent to the widest possible range of persons. As a result, today’s entrepreneurs will be transformed into administrators of access to the computer and into entrepreneurs of the non-digital, utility sector of the economy.Practical significance: the main provisions and conclusions of the article can be used to develop measures to maintain business activity in the new conditions.